Política econômica e distribuição da renda: uma análise comparativa entre Brasil e Chile - Pedroso, Ledi Cerdote (2007)
The development of the capitalism, in Brazil and Chile, deeply was marked by the process of concentration of the income and the wealth. With the evolution of this social system diverse theories they had been appearing aiming at to explain the origins and causes of this phenomenon. Between these theories, the marxist and the estruturalist present more adequate arguments to understand the economic and social formation of these countries, as well as the current distributive situation. The objective of the research is to discourse on the main impacts of the economic policies on the distribution of the income in both the countries. One searchs for intermediary of a bibliographical revision and analysis statistics of the main economic and social pointers to understand this process since respective regimes military. In Brazil of 1960 the 1990, a constant rise in the income concentration was observed and, from 1990, with the adoption of neoliberal politics, this conjuncture did not it if modified. Thus being, it was verified that as much in periods of height in the economic growth how much in periods of economic contraction the phenomenon of the income concentration was always present in the Brazilian society. The Chilean experience is a little different, therefore this country between 1970/1973 it lived deeply a period of great social transformations, with significant improvements in the distribution of the income, this process was ephemeral, since in 1973 the military blow occurs, this regimen is extended up to 1989 provoking significant alterations in the economic and social structure of the country, of which intensified the process of concentration of the income. From 1990, Chile adopted democracy again, thus the governmental authorities comes back to be worried about the social matters. However the structure of the distribution of the income did not present alterations. Equally, one evidenced that the implemented economic policies had had fort influence in the distribution of the income, special orthodox and the neoliberal ones that had aggravated the distributive situation still more.